The gender difference in the effects of air pollution on the risk of spinal osteoarthritis in Chinese middle-aged and older adults: a prospective cohort study in China - Zhou, Jian; Guo, Guanghui; Liu, Tao; Zhu, Zhenjun (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to investigate whether exposure to multiple ambient air pollutants (PM1, PM2.5, PM10, O₃, and NO₂) elevates the risk of spinal osteoarthritis among middle-aged and older adults in China, and to further determine if there are gender-specific differences in vulnerability.MethodsA total of 7,663 participants aged 45 years and older, drawn from the China Health and Retirement Longitudinal Study (CHARLS), were followed from 2011 to 2020. Individuals free of spinal osteoarthritis at baseline were included. Annual mean concentrations of PM1, PM2.5, PM10, O₃, and NO₂ were extracted from the China High Air Pollutants (CHAP) dataset at a 1 km resolution (10 km for NO₂ in some years). Spinal osteoarthritis was identified via self-reported, physician-diagnosed cases involving the spine. Time-varying Cox proportional hazards regression models were used to evaluate hazard ratios (HR) and 95% confidence intervals (CI) per 10 μg/m3 increase in pollutant concentrations. All analyses accounted for demographic, socioeconomic, lifestyle, and spatial/seasonal factors, and explored potential effect modification by gender.ResultsDuring the median 7-year (IQR: 4–9 years) follow-up, 1,556 participants newly reported spinal osteoarthritis. After adjusting for confounders, each 10 μg/m3 increment of PM1, PM2.5, PM10, and NO₂ was associated with a significant rise in the incidence of spinal osteoarthritis (13.8, 6.8, 5.1, and 17.4%, respectively), while O₃ showed a weaker and non-significant effect (1.1%). Notably, stratified analyses revealed that female participants exhibited pronounced vulnerability to PM1, PM2.5, PM10, and NO₂ exposures, whereas the associations in males were not statistically significant.ConclusionThis prospective study indicates that higher concentrations of particulate matter and traffic-related pollutants may contribute to an elevated risk of spinal osteoarthritis, particularly among women. These findings underscore the importance of incorporating musculoskeletal health into air quality management and highlight the value of targeted interventions—such as reducing ambient pollution and monitoring high-risk groups—to mitigate the burden of spinal osteoarthritis in rapidly urbanizing areas.